2017
DOI: 10.24001/ijaems.3.4.14
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Biomass of Leaves of Water Hyacinth (Eichhornia crassipes) as Reducing Agents for the Synthesis of Nanoparticles of Gold and Silver

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…This could be due to increased formation or agglomeration of AgNPs-GA. This finding is consistent with another study that concluded small-sized metal nanoparticles formed at pH 3.0 and 4.0 would bind to many functional groups and nucleate metal ions [ 40 ].…”
Section: Resultssupporting
confidence: 93%
“…This could be due to increased formation or agglomeration of AgNPs-GA. This finding is consistent with another study that concluded small-sized metal nanoparticles formed at pH 3.0 and 4.0 would bind to many functional groups and nucleate metal ions [ 40 ].…”
Section: Resultssupporting
confidence: 93%
“…Known for their rapid growth and invasive nature, water hyacinths pose significant environmental challenges by clogging waterways and depleting oxygen levels in aquatic ecosystems [ 40 , 41 ]. Utilizing water hyacinth biomass for the synthesis of AgNPs not only provides a sustainable and eco-friendly method for nanoparticle production but also offers a potential solution to mitigate the environmental pollution caused by this invasive species [ 42 , 43 , 44 , 45 , 46 , 47 ]. The abundant polyphenols and flavonoids present in water hyacinths can act as both reducing and stabilizing agents, making them an ideal candidate for green synthesis [ 48 ].…”
Section: Introductionmentioning
confidence: 99%